ANALISIS KONDISI FISIK PEMAIN FUTSAL PUTRA KABUPATEN BLITAR PADA PRA PORPROV JAWA TIMUR 2019 - BAHTIAR, YUSUF; FARUK, MOHAMMAD (Jurnal Prestasi Olahraga, 2019)
ABSTRAC ANALYSIS OF PHYSICAL CONDITIONS FUTSAL MEN PLAYERS BLITAR DISTRICT ON EAST JAVA PRA PORPROV 2019 Nama : Yusuf BahtiarNIM : 13060474082Program Studi : S-1 Sports Coaching EducationJurusan : Sports Coaching EducationFakultas : Sports ScienceNama Lembaga : State University Of SurabayaPembimbing : Mohammad Faruk, S.Pd., M.KesThis study raised the issue of the physical condition futsal players in Blitar Regency. The purpose of this research is to determine the physical conditions in the form of endurance, power, speed and agility in male futsal players in Blitar District. The research used is descriptive quantitative with one shot method research. The sample uses data on the amount needed for a team of 15 people. This research instrument uses MFT (Multistage Fitness Test) for ability, long jump for strength, runs 30 meters for speed, and illinois agility run for agility.The results of research endurance MFT (Multistage Fitness Test) mean results 38,706 ml/kg/minute. Players who get an average category of 26.70% are 4 players. fairly category of 46.60% of 7 players. While the players who are in the poor category (poor) 26.70% are 4 players. Power Standing Long Jump test an mean of 241.53 cm. Players who get a very good category of 6.60% are 1 player. Players get 46.70% good categories as many as 7 players. While players get enough categories of 46.70% many as 7 players.The 30 meter running speed test mean 50 second. players get a moderate category of 46.70% in 7 players. 20% less categories many as 3 players. While players get very few categories 33.30% many as 5 players. The Illinois Agility Run test results mean 16?00 seconds. Above average category 40% many as 6 players. While players get the 60% Average category by 9 players. The results of the analysis of physical conditions concluded that the male futsal team in Blitar had moderate physical conditions because the average obtained in the medium category. So it needs intensive training to improve the physical condition of the players to get more leverage and get the best results. Key Words: Physical Condition, Futsal, Blitar District